Capturing School Context Characteristics Using the Job Demands-Resources Model: Adaptation and Validation - Bing Li; Zheng Li (International Journal of Evaluation and Research in Education (IJERE), 2022)
Work environments play a key role in teachers’ professional development. However, instruments assessing teachers’ work context are still lacking. The principal objective of the present study was to validate a Work Environments Inventory for Teachers (WEIT) constructed based on the Job Demands-Resources (JD-R) model. Two studies were conducted involving two independent samples totaling 696 (232 for Study 1 and 464 for Study 2) school teachers in Mainland China. Both exploratory and confirmatory factor analyses were employed to cross-validate the WEIT. The eternal construct validity of the WEIT was checked through investigating its connection with the Thinking Styles in Teaching Inventory. Findings indicated the WEIT is an adequate measure to map the characteristics of work environments for school teachers. Limitations of the present research and implications for future studies are discussed.